2015
DOI: 10.1002/2015gl065826
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal response to a volcano‐tectonic earthquake swarm, Lassen, California

Abstract: The increasing capability of seismic, geodetic, and hydrothermal observation networks allows recognition of volcanic unrest that could previously have gone undetected, creating an imperative to diagnose and interpret unrest episodes. A November 2014 earthquake swarm near Lassen Volcanic National Park, California, which included the largest earthquake in the area in more than 60 years, was accompanied by a rarely observed outburst of hydrothermal fluids. Although the earthquake swarm likely reflects upward migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…The finding is consistent with the hypothesis that large earthquakes may breach aquitards in groundwater systems to depths of several km. Finally, the migration of seismic swarms was used to infer increases of the vertical permeability at depths of ∼20 km [e.g., Ingebritsen and Manning , ; Ingebritsen et al ., ] assuming that the migration of seismic swarms reflects the diffusion of pore pressure.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The finding is consistent with the hypothesis that large earthquakes may breach aquitards in groundwater systems to depths of several km. Finally, the migration of seismic swarms was used to infer increases of the vertical permeability at depths of ∼20 km [e.g., Ingebritsen and Manning , ; Ingebritsen et al ., ] assuming that the migration of seismic swarms reflects the diffusion of pore pressure.…”
Section: Previous Studiesmentioning
confidence: 99%
“…These observations have suggested that earthquakes dynamically affect permeability of the Earth’s crust 20 , 21 . Carbon dioxide (CO 2 ) emissions were observed in association with seismicity in the case of the Matsushiro swarm 9 in Japan or, recently, at the Lassen volcano 22 (Cascades Range, USA) and in the Eger Rift 23 (Czech Republic), which suggests connection between the mid-crust and the ground surface through gas transport. However, such examples so far were only observed in the presence of magmatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…There are examples where ground deformation due to mass discharge or the subsurface migration of hot fluids has been detected at volcanichydrothermal systems that can cause phreatic eruptions (e.g., Nakaboh et al 2003;Maeda et al 2017;Doke et al 2018;Miller et al 2018;Kobayashi et al 2018). A number of authors have also discussed the behavior of volcanichydrothermal systems during non-eruptive unrest events using ground deformation data, gravity changes, geomagnetic changes, and heat flux changes (e.g., Fournier and Chardot 2012;Ingebritsen et al 2015;Currenti et al 2017;Tanaka et al 2017).…”
Section: Introductionmentioning
confidence: 99%